Nas entranhas do bumba meu boi: políticas e estratégias para botar o boi de Leonardo na rua - SILVEIRA, Marla de Ribamar Silva (2014)
The present study investigated the main strategies and politics, internal and external, articulated and developed by mistress/owner of Bumba meu boi of Liberdade Boi of Leonardo, to ensure the legacy left by its father, Leonardo , great teacher and symbol of traditional Boi of Maranhão and eminence of great prestige accent zabumba. Legacy that matches his attitude, loyalty and commitment to the promise that it is his duty to put the Boi on the street. To try to identify and interpret the settings that involve the universe of Maranhão popular culture, we broke into a grounded ethnographic work supported by the theoretical assumptions of the Cultural Theory of Geertz (2012), having as its guideline, however, to lead to the identification and analysis of the strategies and policies developed internally and externally in Boi , the principles of the Theory of Marcel Mauss (2003) on social exchanges or gifts, and identifying, on that path, the organizational culture undertaken by Leonardo and updated by Regina, heiress of the Boi, approaching dynamics of a traditional cultural family organization, of modern organizational logic compared to social, contemporary political and economic transformations.